BIOCHEMICAL PROCESSES AND STRUCTURES IN KIDNEY FUNCTION - Khodzhieva Dilrabo Kamilzhonovna (Web of Journals Publishing, 2025)
The kidneys play a critical role in maintaining bodily homeostasis by carrying out various essential functions, such as filtering the blood, regulating water-electrolyte balance, acid-base homeostasis, and excretion of waste products. These functions are supported by biochemical reactions that occur within the kidneys and ensure their basic physiological processes, including homeostasis, endocrine activity, and metabolic processes.
Keywords: Kidney biochemistry, structural processes, glomerular filtration, tubular reabsorption, metabolite excretion, electrolyte balance, acid-base state, protein metabolism, lipid metabolism, nitrogen metabolism, homeostasis regulation, renin-angiotensin system, nephron.